The two-dimensional laminar boundary layer at hypersonic speeds - Nonweiler, T. (College of Aeronautics, Cranfield, 1953)
A numerical solution is found for the equations governing the motion of a two-dimensional laminar boundary layer, in the absence of a pressure gradient, which would be valid if the flight Mach number is very high (i.e. M2>>1). The effects of surface slip, and the finite thickness of the boundary layer are shown to be negligible if the Reynolds Number (R) exceeds about 105, and are neglected. Continues …